UPAYA MENINGKATKAN MINAT BELAJAR DAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS MELALUI MODEL QUICK ON THE DRAW - MONICA KHOIRUNNISA (TEACHER : Jurnal Inovasi Karya Ilmiah Guru, 2021)
This research is a Classroom Action Research with two analytical techniques, namely qualitative analysis and descriptive statistical analysis to analyze students' interest in learning and mathematical problem solving abilities. Interest in learning is an individual's interest in a process that produces changes in behavior, meanwhile, mathematical problem solving ability is the ability to be able to solve questions or problems in everyday life. The quick on the draw model is a learning to master material concepts that can increase students' enthusiasm and enthusiasm in learning because of teamwork and speed through question cards and question sets. Based on the results of research and discussion, it is known that the quick on the draw model can increase learning interest and mathematical problem solving ability with two cycles. The results of the average percentage of teacher activity observation sheets increased by 16.18% which in the first cycle was 75.98% to 92.16% in the second cycle. Then, the results of the average percentage of student activity observation sheets increased by 19.12% from 72.55% in the first cycle to 91.67% in the second cycle. In addition, the problem solving ability also increased by 26.54% from 40.88% in the first cycle to 67.42% in the second cycle. ABSTRAKPenelitian ini merupakan Penelitian Tindakan Kelas dengan dua teknik analisis, yaitu analisis kualitatif dan analisis statistik deskriptif untuk menganalisis minat belajar dan kemampuan pemecahan masalah matematis siswa. Minat belajar merupakan ketertarikan individu dalam suatu proses yang menghasilkan perubahan tingkah laku, sedangkan, kemampuan pemecahan masalah matematis adalah kemampuan untuk dapat menyelesaikan pertanyaan-pertanyaan atau masalah dalam kehidupan sehari-hari. Model quick on the draw merupakan suatu pembelajaran untuk menguasai konsep-konsep materi yang dapat meningkatkan antusiasme dan semangat siswa dalam belajar karena adanya suatu kerja tim dan kecepatan melalui adanya kartu soal dan set pertanyaan. Berdasarkan hasil penelitian dan pembahasan, diketahui jika model quick on the draw dapat meningkatkan minat belajar dan kemampuan pemecahan masalah matematis dengan dua siklus. Hasil rata – rata prosentase lembar observasi aktivitas guru meningkat sebesar yang pada siklus I sebesar menjadi di siklus II. Kemudian, hasil rata – rata prosentase lembar observasi aktivitas siswa mengalami peningkatan sebesar yang awalnya di siklus I menjadi di siklus II. Selain itu, kemampuan pemecahan masalahnya juga meningkat dari di siklus I menjadi di siklus II.